EVALUATION OF LENGTH-WEIGHT RELATIONSHIP OF FISH SPECIES OF EBONYI RIVER, NIGERIA - UDE, E.F.; UGWU, L.L.C.; MGBENKA, B.O.; NWANI , C.D. (Nigerian Journal of Fisheries, 2011)
A study was conducted on the fishes of Ebonyi River to determine their length – weight relationships (LWR). Specimens of various fish species caught from the river were obtained from fishers on a monthly basis for 18 months. The values of the exponent b in the LWR (W=aL b ) varied between 1.4 and 3.5 for Ariid species, 0.9 and 5.3 for Characiid species, 2.4 and 3.4 for Cichlid species, 4.3 and 11.1 for Clariid species, 2.4 and 3.9 for Mormyrid species and between 2.7 and 2.8 for species of the family Schilbeidae. The b values recorded for Oreochromis niloticus, Schilbe mystus, Siluranodon auritus, Tilapia dageti and Hemichromis fasciatus were all isometric. Arius heudeloti, Labeo coubie, Alestes chaperi, Tilapia zilli and Mormyrus rume each had b values that are negatively allometric. Similarly, the b values recorded for the remaining species were positively allometric. The values of their various intercepts (a) and correlation coefficients (r) are also presented. In the light of these observations it was concluded that the data generated will form a baseline tool for enhanced fisheries management and utilization of the species that are of aquaculture importance to improve fish production in an economy where majority of the populace are undernourished.